Self-construal priming reconsidered: Comparing effects of two commonly used primes in the UK and China - Yang, Shengyu; Vignoles, Vivian L (Open Science Journal, 2020)
Self-construal priming was devised to mimic the effects of chronic cross-cultural differences. Primes designed to activate independent/interdependent self-construals have been found to affect numerous culturally relevant outcomes. However, researchers have rarely checked precisely what these primes activated, nor tested their cross-cultural equivalence. We compared two common priming tasks, Similarities vs. Differences with Family and Friends (SDFF) and Sumerian Warrior Story (SWS), across seven dimensions of independence/interdependence among 118 British and 178 Chinese participants. The two tasks activated different combinations of self-construal dimensions. SWS showed a similar pattern of effects across cultures, whereas SDFF more strongly affected Chinese participants. Neither manipulation closely mimicked the pattern of pre-existing cross-cultural differences between samples. We propose researchers should develop more precisely targeted self-construal primes.